Establishing a clinical high‐risk program in Tunisia, North Africa: A pilot study in early detection and identification. Issue 6 (21st January 2021) - Ventura, Joseph; Jouini, Lamia; Aissa, Amina; Larnaout, Amine; Nefzi, Rahma; Ghazzai, Malek; Jelili, Sélima; Fekih‐Romdhane, Feten; Ouali, Uta; Nacef, Fethi
Abstract: Background: Early identification and prevention research has provided huge advances in our understanding of early screening and identification of young people at clinical high‐risk (CHR). Most of these procedures were developed in high‐income countries, yet middle‐income countries in North Africa such as Tunisia can benefit from these empirically‐based assessment approaches. Methods: Using established procedures, nine Tunisian psychiatric raters were trained on structured assessments: the CAARMS, BPRS, and SCID to high standards of interrater reliability. These raters developed a clinical high‐risk program (CHiRP) in Tunisia and recruited 10 patients who were exhibiting possible signs of CHR. These patients were evaluated to determine if they met criteria for a CHR group, such as Attenuated Psychosis. Results: Trained raters met the following interrater reliability criteria for the CAARMS and BPRS (ICC = .80 or greater) and the SCID (Kappa = .75 or greater). Of 10 pilot patients, six were classified as CHR and belonging to the Attenuated Psychosis Group. One of the six patients converted to psychosis 3 months after study entry for a conversion rate of 17% which is comparable with currently published rates globally. Discussion: The first CHR program has been established in Tunisia, a middle‐income country using methods developed in high income countries. Efforts aimed at assembling a group of prevention‐oriented psychiatrists, obtaining administrative support, and training raters to high levels of interrater reliability were successful. The feasibility was demonstrated for screening, assessing, treating, and following‐up of 10 CHR patients suggesting that conversion rates are comparable to those of Western and European countries.